Quorum-Sensing Antagonistic Activities of Azithromycin in Pseudomonas aeruginosa PAO1: a Global Approach - Nalca, Yusuf (American Society for Microbiology, 2006)
The administration of macrolides such as azithromycin for chronic pulmonary infection of cystic fibrosis patients has been reported to be of benefit. Although the mechanisms of action remain obscure, anti-inflammatory effects as well as interference of the macrolide with Pseudomonas aeruginosa virulence factor production have been suggested to contribute to an improved clinical outcome. In this study we used a systematic approach and analyzed the impact of azithromycin on the global transcriptional pattern and the protein expression profile of P. aeruginosa PAO1 cultures versus those in untreated controls. The most remarkable result of this study is the finding that azithromycin exhibited extensive quorum-sensing antagonistic activities. In accordance with the inhibition of the quorum-sensing systems, virulence factor production was diminished and the oxidative stress response was impaired, whereas the type III secretion system was strongly induced. Moreover, P. aeruginosa motility was reduced, which probably accounts for the previously observed impaired biofilm formation capabilities of azithromycin-treated cultures. The interference of azithromycin with quorum-sensing-dependent virulence factor production, biofilm formation, and oxidative stress resistance in P. aeruginosa holds great promise for macrolide therapy in cystic fibrosis. Clearly quorum-sensing antagonist macrolides should be paid more attention in the management of chronic P. aeruginosa infections, and as quorum-sensing antagonists, macrolides might gain vital importance for more general application against chronic infections.